On stinging relationships - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The System-wide Initiative on Malaria and Agriculture (SIMA) is organising a one-day seminar on its theme, on 20 November 2002 during the Third MIM Pan-African Malaria Conference in Arusha, Tanzania.SIMAPO Box 2075, Colombo, Sri LankaEmail:...